If I had a song [Bladmuziek] : a song book for childern growing up. - Gifford, Alan (London : Workers' Music Association (WMA), 1954)
Deze brochure bevat volgende liederen
Robin Hood
Henry martin
Bill Bones's Hornpipe
Cosher Bailey's Engine
The Old Man and his Wife
The Wraggle Taggle Gipsies
The blue-tail fly
Pretty little horses
The Fly and the Humble Bee
O can ye sew cushions
Leave her, Johnnie
The old Chisholm Trail
The Shoemaker
The collier's rant
Poor Paddy works on the railway
Fitba' crazy
Our hands are young
The bird with a leaf
The Trafford Road Ballad
The Hammer Song
Ain' goin' study <ar no more
Freedom's Song
Billy Boy
The animals went in
Shule Agra
The Boatman
My bonnie
All trough the night
The Cutty Wren
John Brown's body
Stand up, Diggers all
Van Diemen's Land
People of England
Helvetia's Children
The Birch Tree
The echo of our youth
Hungarian Round
Kookaburra
The Twelve Days of Christmas
Cockles ans mussels
The quartermaster's store
Shenandoah
Clementine
Te Mistrel Boy
Fire down below
Blow the man down
A-roving
Jerusalem
Archief Sylvain Libert
Engels
Partituur
Keywords: liederen; partituren